Alcohol septal ablation gone wrong- case report of a complication of hypertrophic obstructive cardiomyopathy treatment - Radoicic, Dragana; Borzanovic, Dusan; Odanovic, Natalija; Nikolic, Aleksandra; Otasevic, Petar; Ilic, Ivan; Vucinic, Sanja (Journal of Cardiovascular Medicine and Cardiology, 2023)
Alcohol Septal Ablation (ASA) is an interventional procedure that involves injecting ethanol into a targeted septal artery, inducing localized tissue necrosis, and subsequently reducing septal thickness. Our experience highlights this method as an effective therapeutic intervention for symptomatic HOCM patients, providing relief from symptoms and enhancing cardiac function, reducing Left Ventricular Outflow Tract (LVOT) gradient. However, potential complications such as arrhythmia, Left Anterior Descending (LAD) dissection, cardiac tamponade, and coronary artery spasm are rare but necessitate careful patient selection and vigilant post-procedural monitoring. It is a reasonable therapeutic option especially in older patients with favourable coronary anatomy in the absence of mitral valve disease and if it is performed by an experienced operator. We present a case of a 68-year-old man with Hypertrophic Obstructive Cardiomyopathy (HOCM), elevated LVOT gradient, and symptoms despite optimal medical therapy. He underwent alcohol septal ablation which was complicated by alcohol leakage likely via collateral circulation into the distal left anterior descending artery and obliteration of the vessel.